Eficácia de dois herbicidas no controle de capim-capeta - Silva, Carolina Pires da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Devil grass (Sporobolus indicus L.) is an aggressive and difficult-to-control weed that affects pastures in the Amazon, Cerrado, and Atlantic Forest biomes. Originally from India, it has spread throughout Brazil due to its resistance to drought, trampling, and high production of viable seeds. Its low palatability to cattle favors its expansion, reducing pasture productivity. Control is difficult due to the lack of effective herbicides and the wide dispersion of the plant. Chemical control is an alternative, but still requires further research to ensure its efficiency. The present study conducted two experiments, with four replicates per treatment, totaling 20 experimental units per experiment. The treatments included two herbicides evaluated separately (atrazine and atrazine+mesotrione) applied at four different doses (1/4D, 1/2D, 1D, and 2D), in addition to the control without herbicide application. The evaluations were performed at 7, 14, 21 and 28 days after application (DAA). After the last evaluation, the remaining plants were cut and placed in a greenhouse with forced air circulation at 65°C for 96 hours to obtain the dry mass of the aerial part. The data obtained were subjected to analysis of variance (ANOVA) by the F test, and the data related to biomass were calculated as the reduction in dry biomass in percentage in relation to the control. The results showed that isolated atrazine (Atraer WG), even in fractional doses, caused highly effective control, reaching 100% control up to 28 DAA with total reduction of biomass. The combination atrazine + mesotrione (Calaris) resulted x in satisfactory control at commercial or higher doses; however, in fractional doses, regrowth and less residual effect of the product occurred.

Devil grass (Sporobolus indicus L.) is an aggressive and difficult-to-control weed that affects pastures in the Amazon, Cerrado, and Atlantic Forest biomes. Originally from India, it has spread throughout Brazil due to its resistance to drought, trampling, and high production of viable seeds. Its low palatability to cattle favors its expansion, reducing pasture productivity. Control is difficult due to the lack of effective herbicides and the wide dispersion of the plant. Chemical control is an alternative, but still requires further research to ensure its efficiency. The present study conducted two experiments, with four replicates per treatment, totaling 20 experimental units per experiment. The treatments included two herbicides evaluated separately (atrazine and atrazine+mesotrione) applied at four different doses (1/4D, 1/2D, 1D, and 2D), in addition to the control without herbicide application. The evaluations were performed at 7, 14, 21 and 28 days after application (DAA). After the last evaluation, the remaining plants were cut and placed in a greenhouse with forced air circulation at 65°C for 96 hours to obtain the dry mass of the aerial part. The data obtained were subjected to analysis of variance (ANOVA) by the F test, and the data related to biomass were calculated as the reduction in dry biomass in percentage in relation to the control. The results showed that isolated atrazine (Atraer WG), even in fractional doses, caused highly effective control, reaching 100% control up to 28 DAA with total reduction of biomass. The combination atrazine + mesotrione (Calaris) resulted in satisfactory control at commercial or higher doses; however, in fractional doses, regrowth and less residual effect of the product occurred.
EFFICACY OF TWO HERBICIDES IN CONTROLLING BLACKBERRY GRASS
Keywords: Atrazina; Controle; Capim